Nutritional status and nutrient adequacy against serum prolactin levels in lactating mothers during the COVID-19 pandemic - Giyawati Yulilania Okinarum; Lestariningsih Lestariningsih; Afroh Fauziah (Journal of Health Technology Assessment in Midwifery, 2021)
The COVID-19 pandemic is creating global disruption, every area of life is touched. One area that has an impact, is breastfeeding, which is caused by nutritional status and nutrient adequacy during the pandemic, this condition affects prolactin release. Prolactin hormone stimulates and initiatiates of milk secretion. Midwives employed in maternal-child settings play a pivotal role in facilitating and supporting lactating mothers. This study aimed to identify and analyze the nutritional status and nutrient adequacy against serum prolactin levels in lactating mothers during the COVID-19 pandemic. Sixty lactating mothers from Sleman Regency and Yogyakarta city participated in this cross-sectional study. All were between 0-3 postpartum months. A single blood sample was collected from women at 7-9 am. Serum samples were stored at 2-8⁰C before the prolactin assay by using VIDAS®. Data analysis using Kruskal Wallis followed by Post-Hoc Mann Whitney. Results found a statistically significant difference in serum prolactin levels between underweight vs normoweight and normoweight vs overweight (p0.05), but there was no significant difference in serum prolactin levels between underweight vs overweight (p0.05). Significant differences in serum prolactin levels also found in the nutrient adequacy (energy, carbohydrate, protein, and fat) (p 0.05). Thus, normoweight and adequate macronutrient during breastfeeding in the COVID-19 pandemic situation had better serum prolavtin levels than underweight, overweight and inadequate macronutrient.